Grape and wine flavonoid composition in transgenic grapevines with altered expression of flavonoid hydroxylase genes - Robinson, Simon; Bogs, Jochen (Australian journal of grape and wine research, 2019)
Background and Aims Grape flavonoids impart colour and mouthfeel to wines. This work aimed to understand how genetic manipulation of the hydroxylation of flavonoids affected grape flavonoid composition and wine properties. Methods and Results We produced transgenic grapevines with decreased expression of flavonoid 3′-hydroxylase (F3′H) and flavonoid 3′5′-hydroxylase (F3′5′H) to investigate how this altered the composition of flavonoids in grapes and wine. Grapes from transgenic grapevines with decreased expression of F3′5′H genes had a concentration of anthocyanin and skin tannin similar to that of Shiraz Controls but had increased seed tannin and a greatly decreased proportion of trihydroxylated anthocyanin and tannin. Lines with decreased expression of F3′H had a decreased concentration of seed tannin and an increased proportion of trihydroxylated flavonoids. When expression of both F3′H and F3′5′H was decreased, concentration of anthocyanin and tannin in the grapes was decreased to 20-30% of the Shiraz Controls. Wines made from grapes with decreased expression of F3′5′H had lower wine colour, and a lower concentration of anthocyanin, tannin and phenolic substances. Conclusions In grapes, the flavonoid pathway does not effectively use monohydroxylated intermediates so F3′H and F3′5′H are required to produce dihydroxylated and trihydroxylated intermediates. The hydroxylation status of flavonoids in grapes determines grape and wine colour and tannin composition. Significance of the Study The composition as well as the total amount of anthocyanin and tannin in grapes is important for wine colour and quality. The expression of genes encoding F3′H and F3′5′H in grapes is dependent on viticultural factors including temperature, light exposure and vine water stress, providing the potential to manipulate flavonoid composition of existing cultivars in the vineyard.